A rational cotangents of the angles of a triangle - Mazėtis, Edmundas; Melničenko, Grigorijus (Lietuvos matematikos rinkinys, 2014)
We investigate how rational values cotangents angles of a triangle influence of its properties. The main result: cotangents of any two angles of a triangle are rational then, and only then, when a triangle similar to a triangle whose squares of sides are integer and twice the area is an integer.
Keywords: Heronian triangles; pseudo Heronian triangles; integer lattice